Adapting parent engagement strategies for an evidence‐based parent‐mediated intervention for young children at risk for autism spectrum disorder. Issue 4 (1st April 2020) - Haine‐Schlagel, Rachel; Rieth, Sarah; Dickson, Kelsey S.; Brookman‐Frazee, Lauren; Stahmer, Aubyn
Abstract: Aims: Aims included (a) characterizing provider feedback on parent engagement strategies integrated into a parent‐mediated intervention for toddlers at risk for autism spectrum disorder (ASD) and (b) identifying provider characteristics that predict attitudes about parent engagement strategies. Methods: A mixed method approach was utilized, including gathering quantitative data via survey (breadth) and collecting qualitative data via interview (depth). Acceptability, utility, appropriateness, sustainment, generalizability, and perceived effectiveness were examined. Fourteen agency leaders and 24 therapists provided input. Results: Providers perceived the integration of parent engagement strategies as having a positive impact on implementation. Providers considered the strategies to be acceptable, appropriate, and effective, though barriers of time and complexity were noted. Provider characteristics did not consistently predict attitudes about the engagement strategies. Conclusions: Incorporating parent engagement strategies into parent‐mediated interventions for ASD is well‐received by providers and may improve quality of service delivery for families served in early intervention for ASD.